Executive compensation stickiness and ESG performance: The role of digital transformation - Chen, Lifeng; Mao, Chuanmei; Gao, Yuying (Frontiers in Environmental Science, 2023)
The implementation of environment, social and governance approaches at the enterprises’ level remain insufficient. Further, an urgent attention needs to be paid on the fully application of digital solutions for sustainable development, resource allocation as well as improving social responsibility. Encouraged by the asymmetric effect between executive compensation stickiness(ECS) and corporate performance, managers are more willing to improve the level of corporate environmental, social and governance (ESG) indices by digital transformation (DT). This study employs 18,098 observations from Chinese A-share listed companies to examine the impact of ECS on ESG indicators. Our results show: ECS can significantly improve the ESG scores, where DT played a partial mediating role within this promotion. We further examine this relationship by Bootstrap and Sobel methods, all empirical results are robust and credible. Our findings provides more practical enlightenment at management aspect for improving environmental performance through digital transformation.